Pro HTML5 Games - Shankar, Aditya Ravi (Apress : Imprint: Apress, 2012)
Build your next game on a bigger scale with Pro HTML5 Games. This book teaches you the essentials of advanced game programming in HTML5. You'll learn techniques that you can transfer to any area of HTML5 game development to make your own professional HTML5 games! Led by an expert game programmer, you'll build two complete games in HTML5: a strategy puzzle game based on the Box2d physics engine and in the style of Angry Birds and a real-time strategy (RTS) game complete with units, buildings, path-finding, artificial intelligence, and multiplayer support. In the process, you'll learn how to do the following: Create realistic physics in your game by incorporating the Box2d physics engine Design large worlds with lots of characters and let users interact with them Use sprite sheets, panning, parallax scrolling, and sound effects to build a more polished game Incorporate pathfinding and steering to help characters navigate through your world Create challenging levels with intelligent enemies by using decision trees, state machines, and scripted events Add multiplayer in your games using Node.js and the WebSocket API This book will help you take your HTML5/JavaScript programming experience to the next level. It gives you the knowledge and skills you need to develop more complex, bolder games and become an HTML5 games pro.